2009
DOI: 10.1126/science.1169678
|View full text |Cite
|
Sign up to set email alerts
|

A Ferroelectric Oxide Made Directly on Silicon

Abstract: Metal oxide semiconductor field-effect transistors, formed using silicon dioxide and silicon, have undergone four decades of staggering technological advancement. With fundamental limits to this technology close at hand, alternatives to silicon dioxide are being pursued to enable new functionality and device architectures. We achieved ferroelectric functionality in intimate contact with silicon by growing coherently strained strontium titanate (SrTiO3) films via oxide molecular beam epitaxy in direct contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
254
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 364 publications
(261 citation statements)
references
References 29 publications
7
254
0
Order By: Relevance
“…This can be avoided only by carefully adjusting growth temperatures and supplying just the right amount of oxygen at precisely the right time. Still, progress has been made and the quality of oxide films on silicon has been improving steadily 11 . "Even advanced oxide films such as LaAlO 3 /SrTiO 3 heterostructures have now been grown on silicon, " says Mannhart.…”
Section: Just One Small Pushmentioning
confidence: 99%
“…This can be avoided only by carefully adjusting growth temperatures and supplying just the right amount of oxygen at precisely the right time. Still, progress has been made and the quality of oxide films on silicon has been improving steadily 11 . "Even advanced oxide films such as LaAlO 3 /SrTiO 3 heterostructures have now been grown on silicon, " says Mannhart.…”
Section: Just One Small Pushmentioning
confidence: 99%
“…Recently, thin-film deposition techniques have been advanced, enabling the growth of epitaxial heterostructures with atomically controlled interfaces, such as multi-layers [23], superlattices [24,25] and ultrathin films [26,27]. Owing to advanced deposition techniques, studies using strain engineering have improved, and it has been shown experimentally and theoretically that such strain can even stabilize systems in novel non-bulk phases [28][29][30][31][32].…”
Section: Nanoscale Strain Gradient In Epitaxial Oxide Thin Films (A) mentioning
confidence: 99%
“…T he presence of functional properties in many perovskite materials 1,2 has pushed the development of integrating such crystals directly on silicon (Si) to realize a variety of new devices 3 . Since the first methods to epitaxially deposit perovskite thin films on Si were established 4 , the growth process has been carefully optimized 5 and single crystalline layers were fabricated even on large-scale 8 00 substrates 6 .…”
mentioning
confidence: 99%